Diseño de un centro de protección canino en situación de calle mediante la arquitectura biofilica en Babahoyo - Nagua Freire, Oralia Mariana (2025)
This research focuses on the design of a Protection Center for Street Dogs based on biophilic architecture principles in the city of Babahoyo, responding to the urgent need caused by the indiscriminate growth of the canine population in the urban área. Due to its geographical location and climatic conditions characterized by high temperatures and humidity Babahoyo requires not only functional architectural solutions, but also sustainable ones. Therefore, this project incorporates local native materials and traditional construction techniques, adapted to the specific conditions of the selected site, as a primary strategy to achieve thermal comfort.............